Development of Bilingual Picture Storybooks with a Science Content Orientation for Elementary School - Ni Putu Trisna Dewi Andyani; Putu Nanci Riastini; Luh Sri Surya Wisma Jayanti (Universitas Pendidikan Ganesha, 2025)
Science learning in elementary schools is hindered by the limited availability of engaging, relevant, and bilingual learning resources, resulting in less optimal understanding of science concepts and English skills. This study aims to: a) describe the characteristics of Elementary School Science Content-Oriented Bilingual Picture Story Books needed by students, b) produce their design, c) test their validity, and d) test their practicality. The study employed the ADDIE model—analysis, design, development, implementation, and evaluation—with data collected through interviews, observations, and questionnaires, and analyzed using qualitative and quantitative methods. Validity testing yielded scores of 0.94 from material and media experts, and 0.95 from language experts, all in the “very high” category. Practicality testing showed teacher response scores of 91.11% and student responses of 96.50%, both categorized as “very good.” The findings indicate that the book is feasible and practical for use as a science learning resource. Its implication is the potential to enhance science learning and improve students’ English skills, provided teachers adapt its use to students’ characteristics and abilities to ensure optimal learning outcomes.